Incidence of a hypermedia educational material on the Teaching and Learning of Mathematics - Río, Laura Sombra del (2019)
The use of hypermedia educational materials in education has gained relevance in recent years and is the object of numerous research activities. In the context of teaching and learning Mathematics, there are diverse works detailing their potential to improve both student learning and student attitude towards the subject. In this article, the results obtained through a case study carried out in a frst-year course of Mathematics at a School of Engineering are shared, for which a hypermedia material was designed and then its impact in the classroom was analysed. To that end, a quanti-qualitative analysis framework was designed. An experience was carried out with two groups of students: one of these (n=101) used this material, and the other (n=111) served as control group. The students gave a positive overall assessment as regards to the experience carried out with the hypermedia material, but not to the extent expected. However, observations and the interviews carried out with the educators revealed that the hypermedia material positively contributed to several student learning aspects: it allowed using a mathematical software application as an exploratory tool and it promoted critical thinking among the students, who used the application to check their pen-and-paper work, using the semiotic representation conversions.